Exploring sustainable healthcare waste management implementation in teaching hospitals in Malaysia - Timothy Kurannen Baaki; Mohamad Rizal Baharum; Azlan Shah Ali; Mohd Hasni Jafa'ar (Penerbit UKM, 2020)
There are growing expectations for healthcare organizations to take active steps and introduce sustainable approaches to healthcare waste management (HCWM). This study investigated sustainable healthcare waste management (SHCWM) in two university teaching hospitals in Malaysia. The objectives of the study were to identify current practices and SHCWM initiatives as well as examine the training and knowledge of hospital staff on sustainable healthcare waste management. Following a questionnaire survey of 243 senior hospital staff, the study found that sustainable healthcare waste management initiatives were being implemented in the healthcare facilities (HCFs) surveyed. Descriptive statistics using frequency distributions and mean rank analysis were used to analyze data from the 243 respondents. The findings revealed that proper segregation and sorting, purchasing supplies that generate less hazardous waste, education/awareness about material reuse and recycling, purchasing environmentally friendly products, and encouraging material reuse and recycling through reward were the five initiatives perceived to be most implemented at the HCFs. The study also found that majority of the respondents received training and were highly knowledgeable about the health and environmental risks of HCW as well as SHCWM aspects such as waste minimization. The findings from this study provide an overview of SHCWM in particularly large teaching hospitals in Malaysia and suggests further research for a more comprehensive and wider understanding of SHCWM in HCFs in Malaysia.